2020
DOI: 10.3389/fncom.2019.00085
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Non-linear Directed Information Flow in Schizophrenia by Multivariate Transfer Entropy

Abstract: People living with schizophrenia (SCZ) experience severe brain network deterioration. The brain is constantly fizzling with non-linear causal activities measured by electroencephalogram (EEG) and despite the variety of effective connectivity methods, only few approaches can quantify the direct non-linear causal interactions. To circumvent this problem, we are motivated to quantitatively measure the effective connectivity by multivariate transfer entropy (MTE) which has been demonstrated to be able to capture b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…This can be attempted in future works. For instance (Harmah et al, 2019) in a recent paper, evaluated multivariate TE in people with schizophrenia, and found that multivariate TE outperformed bivariate TE and Granger causality analysis under various signal-to-noise conditions. However, it is to be stressed that this difference between our results and those obtained with multivariate TE are probably not so strong as in other works, since Trentool implements some tools for post-hoc corrections of multivariate effects, i.e., a partial correction of spurious information flow.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attempted in future works. For instance (Harmah et al, 2019) in a recent paper, evaluated multivariate TE in people with schizophrenia, and found that multivariate TE outperformed bivariate TE and Granger causality analysis under various signal-to-noise conditions. However, it is to be stressed that this difference between our results and those obtained with multivariate TE are probably not so strong as in other works, since Trentool implements some tools for post-hoc corrections of multivariate effects, i.e., a partial correction of spurious information flow.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the approach proposed here has the potential to be applicable to the inference of structural and effective connectivity in in vitro and in vivo neuronal circuits with a strong impact on the comprehension of basic mechanisms underlying information acquisition, storage, and transmission in physiological or pathological scenarios. Particular relevance in this regard concerns the investigation of network properties in neurological disorders or pathologies, such as schizophrenia, Alzheimer’s disease, strokes and epilepsy [ 60 , 61 , 62 , 63 , 64 ], where our approach can be useful not only in predicting general features of connectivity but also in identifying the unbalance between excitation and inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, conditional mutual information methods such as momentary TE 67 should be employed to estimate direct causality by conditioning out the effects of possible common drivers. Other alternatives to reduce the effects of common drivers exist 68 71 . Nevertheless, these techniques share the issue of estimation of neural interactions when the number of nodes in the analysis is large.…”
Section: Discussionmentioning
confidence: 99%